The role of social capital in sustainable development the case of selected extension programs in Philippines - Visco, E. S. (Compendium of Human Ecology Researches in the Philippines, 2003)
This research was conducted to determine the role of social capital in the sustainability of selected extension programs of the CHE-UPLB. Results showed that respondents' social capital contributed significantly to the sustainability of the extension programs. The UPLB's credibility as the premier university of the country due to its UPLB's credibility as the premier university of the country due to its recognized academic excellence and outstanding research and extension programs facilitated the institutionalization of some of the programs under study. Similarly, continuous interaction with the stakeholders of the projects under study contributed to the positive attitude and perception towards the projects and each other. While the value of social capital to the academe's development programs under study. Similarly, continuous interaction with the stakeholders of the projects under study contributed to the positive attitude and perception towards the projects and each other. While the value of the social capital are relatively new. With the country's economic state, incessant storm attacks, water and mud flooding and other disasters that caused loss of lives and property to millions of Filipinos, studies recognizing the stakeholder's social capital to the sustainability of development as well as rebuilding lives once again are very relevant and timely.